Simitthus / Chimtou, Tunesien. Die Arbeiten der Jahre 2016 bis 2018 - von Rummel, Philipp; Ardeleanu, Stefan; Beck, Dennis M.; Chaouali, Moheddine; Möller, Heike (e-Forschungsberichte des DAI, 2019)
The ancient town of Simitthus (today Chimtou, Tunisia), known for its important quarries of yellow Numidian marble (giallo antico), has been the object of archaeological research conducted jointly by the Tunisian National Heritage Institute and the German Archaeological Institute in Rome since 1965. This report presents a short overview on the activities at Chimtou in 2016–2018, which were primarily dedicated to publishing the results of the excavations conducted in the 1980s accompanied by measures of capacity building and site management.